2v+6=-4(v+3)

Simple and best practice solution for 2v+6=-4(v+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2v+6=-4(v+3) equation:


Simplifying
2v + 6 = -4(v + 3)

Reorder the terms:
6 + 2v = -4(v + 3)

Reorder the terms:
6 + 2v = -4(3 + v)
6 + 2v = (3 * -4 + v * -4)
6 + 2v = (-12 + -4v)

Solving
6 + 2v = -12 + -4v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '4v' to each side of the equation.
6 + 2v + 4v = -12 + -4v + 4v

Combine like terms: 2v + 4v = 6v
6 + 6v = -12 + -4v + 4v

Combine like terms: -4v + 4v = 0
6 + 6v = -12 + 0
6 + 6v = -12

Add '-6' to each side of the equation.
6 + -6 + 6v = -12 + -6

Combine like terms: 6 + -6 = 0
0 + 6v = -12 + -6
6v = -12 + -6

Combine like terms: -12 + -6 = -18
6v = -18

Divide each side by '6'.
v = -3

Simplifying
v = -3

See similar equations:

| x^3-3x^2-600=0 | | 4a-(2a+4)= | | v^2+14vy+49y^2=0 | | 4(6x+10)=-8(-4x+7) | | -3(x-5)=x-13 | | -(1x-2)-6.5=2.5x+19 | | 6x+17=15x-111 | | 2x+8=4(x-3) | | 2v+6=-4(1v+3) | | 4z=-40 | | x+35=84-74 | | 180-x=2(x+20) | | 180x=2(x+20) | | -5.7p+10.16=-65.08 | | x+20=180-2(x+20) | | 2[x+3]=-4[x+1] | | -3b+ax=x-4 | | x+20=180-(x+20) | | 147-3b^2=0 | | (2b^5-5b^4+8b^3-12b^2+12b-9)= | | 15y-16=7y-15 | | 0.2n+3= | | 3(2x+5)=5x+12 | | 7[3-(-4x-1)]=252x+84 | | 10x-8=102 | | 8x-2(x-5)=x+5 | | 31s+10=-14s | | V^2+12v-24=0 | | 6(2t+5)=4 | | -45=-6(-36-4) | | 7n^2-52n-32=0 | | x^2-x=552 |

Equations solver categories